Analisis Proses Perencanaan Program Pendidikan Nonformal bagi Anak Jalanan di Klinik Jalanan Samarinda - Mustangin Mustangin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2020)
Street children become one of the problems that exist today, so it needs non-formal education efforts through its programs to overcome these problems. To get maximum educational results, a non-formal education program planning strategy is needed for these street children. This study aims to analyze the planning process of non-formal education programs for street children in Klinik Jalanan Samarinda. This study uses a qualitative approach because it will reveal how the non-formal education program planning process is for street children. This type of research is a descriptive study that will produce a description of the focus of the research conducted. Data collection techniques using interviews, observation, and study of documents. While the data analysis technique uses data reduction, data presentation, and drawing conclusions. The analyzing the validity of the data using data triangulation. The results of the study revealed that the planning process carried out by the Klinik Jalanan Samarinda was divided into several processes including the approach to street children as a means of learning citizens. The next process is identifying the learning needs of street children to design non-formal education programs such as what is suitable for street children. Next is the preparation of learning to get an agreement with street children because street children have their preoccupations, so the need for an agreement on the time and place for the implementation of learning.